Occupational therapy in the promotion of health and wellness - Scaffa, Marjorie E., ....-; Pizzi, Michael, ....-; Reitz, S. Maggie, ....- (Philadelphia : F.A. Davis Co., 2010)
Here's the very first text to address this evolving new area of OT practice! It teaches students about health promotion and prevention theory and practice from a wellness rather than an illness perspective. Using “cutting edge” examples, the authors explore how to incorporate this new paradigm into clinical practice and how to develop wellness interventions across the lifespan.
Keywords: Health Behavior; Health Promotion; Occupational therapy